Correlation between physical activity levels and the risk of cognitive impairment in Chinese older adults - Feng-Wei Dong; Feng-Wei Dong; Dong-Hui Wang; Yu-Jie Chang; Li-Xu Tang (Frontiers in Aging Neuroscience)
ObjectiveTo analyze the correlation between the level of physical activity and the risk of cognitive impairment in Chinese older adults aged 60 years and above, and to provide correlational evidence for the development of targeted strategies to prevent cognitive impairment.MethodsThis study used five rounds of longitudinal data from the China Health and Retirement Longitudinal Study (CHARLS) conducted between 2011 and 2020, which included 3,583 older adults aged 60 years and above. Multiple regression models were employed to evaluate the association between varying intensities of physical activity (low-intensity, moderate-intensity, and high-intensity) and the risk of developing cognitive impairment (HR).ResultsIn models that were not adjusted for any variables, the risk of cognitive impairment was reduced by 25.3% in the moderate-intensity physical activity group compared to the low-intensity group (HR = 0.747, 95%CI: 0.617–0.903), and by 11.0% in the high-intensity group (HR = 0.890, 95%CI: 0.798–0.992). In the model that fully controlled for all confounding variables, the risk ratio was further reduced to 30.7% (HR = 0.693, 95%CI: 0.571–0.841) in the moderate-intensity physical activity group and 9.7% (HR = 0.903, 95% CI: 0.809–1.007) in the high-intensity group. Dose–response analysis revealed an optimal strength of association between moderate-intensity physical activity (approximately 2,800 MET-minutes per week) and cognitive health.ConclusionModerate-intensity physical activity can significantly reduce the risk of cognitive impairment among older adults in China. It is recommended that health management and cognitive impairment prevention strategies for this population incorporate moderate-intensity physical activity.